APPLICATION OF LEAN SIX-SIGMA METHOD AND DEMERIT CHART TO MINIMIZE DEFECTIVE PRODUCT - Novia, Ayu; Sari, Rina Filia; Widyasari, Rina (Journal of Mathematics and Scientific Computing With Applications, 2021)
uality control is a form of inspection using certain techniques or methods in decision-making to get the quality standards that have been determined. One type of quality control is using the method of Lean Six Sigma to identify and eliminate waste in activities that are not worth the added value through a continuous increase to reach the level of Six Sigma, then use the demerit control chart as a monitor of the production process. The purpose of the study was to find out how to minimize defects in the 220ml Aqua cup mineral water packaging with the method of Lean Six Sigma and Demerit control chart. With the analysis that has been done, it is known that in the 220ml Aqua Cup product the DPMO value for defects in the 220ml AQUA Cup production process is 22912.83, which is the level of sigma is 3.43 and the process capabilities value is 0.77087 which mean that it still needs a process control for minimizing the product defects.